Perancangan Mesin Press Kaleng Minuman Menggunakan Tenaga Motor Listrik - Sir Anderson; Khairul Amri; Maimuzar Maimuzar; Hanif Hanif; Figo Zubrianto (Jurnal Teknik Mesin, 2023)
Aluminum can waste is becoming more prevalent. There is no trash processing system, and the public does not value recycling. Used-goods collectors may damage themselves by crushing cans with a hammer to reduce volume. To improve the recycling process of aluminum beverage cans, an electric-powered press machine will be designed. The design of this press machine is intended to assist users in the waste treatment process in minimizing space, especially in the trash can storage space, and to make it easier for collectors of recyclables. This equipment is used to compress objects with a driving force. The press machine developed can reduce the volume or dimensions to increase the capacity of transmitting cans, which will subsequently be melted again. Previous research has been based on pneumatic motors and manufacturing techniques that demand a large amount of space and are therefore impractical. Meanwhile, despite having the same power of 1/2 HP, the smaller rotation speed of 272.5 RPM results in a reduced pressing force of 59.17 kgf. The motor was designed to have a power output of 1/2 horsepower and a rotational speed of 1400 revolutions per minute. The transmission system uses a 76.2-millimeter diameter pulley along with a belt that has a type 50 speed reducer ratio of 1:60. A cam, coupled with the speed reducer, moves the pressing cylinder translationally. This enables the pressing cylinder to press up to 1,380 cans per hour. The force required to press the can is 951.57 N.